Prognostic Value of C-Reactive Protein, Glasgow Prognostic Score, and C-Reactive Protein-to-Albumin Ratio in Colorectal Cancer - Zhou, Jiahui; Wei, Wene; Hou, Hu; Ning, Shufang; Li, Jilin; Huang, Baoyue; Liu, Kaisheng; Zhang, Litu (Frontiers in Cell and Developmental Biology, 2021)
Background: Emerging evidence suggests that inflammatory response biomarkers are predictive factors that can improve the accuracy of colorectal cancer (CRC) prognoses. We aimed to evaluate the prognostic significance of C-reactive protein (CRP), the Glasgow Prognostic Score (GPS), and the CRP-to-albumin ratio (CAR) in CRC. Methods: Overall, 307 stage I–III CRC patients and 72 colorectal liver metastases (CRLM) patients were enrolled between October 2013 and September 2019. We investigated the correlationship between the pretreatment CRP, GPS, CAR, and clinicopathological characteristics. The Cox proportional hazard model was used for univariate or multivariate analyses to assess potential prognostic factors. An ROC curve was constructed to evaluate the predictive value of each prognostic score. Establish colorectal cancer survival nomograms based on the prognostic score of inflammation. Results: The optimal cutoff level for the CAR for overall survival (OS) in CRC patients, stage I–III CRC patients and CRLM patients were 0.16, 0.14 and 0.25, respectively. Kaplan–Meier analysis and log-rank tests demonstrated that those with high CRP, CAR, and GPS had a poorer OS in patients with colorectal cancer, both in the cohort of the patients with stage I–III and CRLM patients. In different cohorts of colorectal cancer patients, the AUC of these three markers are all high. Multivariate analysis indicated that location of the primary tumor, pathological differentiation, pretreatment CEA, CRP, GPS, and CAR were independent prognostic factors for OS in stage I–III patients, and that CRP, GPS, and CAR were independent prognostic factors for OS in CRLM patients. Predictors contained in the prediction nomograms included the pretreatment CRP, GPS and CAR. Conclusions: CRP, GPS, and CAR have independent prognostic value in patients with CRC. Furthermore, the survival nomograms based on CRP, GPS, and CAR can provide more valuable clinical significance.